A Study of Fire Drone Extinguishing System in High-Rise Buildings - Kai Wang; Yingfeng Yuan; Mengmeng Chen; Zhen Lou; Zheng Zhu; Ruikun Li (Fire, 2022)
Firefighting in high-rise buildings remains a difficult problem in the world because fire extinguishing equipment and tactics have many deficiencies in dealing with such building fires, especially for buildings higher than 50 m. In the present study, the LY100 fire extinguishing system is taken as an example to introduce the application of the fire drone in the fire control of high-rise buildings. The LY100 fire extinguishing system mainly contains the twin-rotor drone, high-pressure liquid fire extinguishing equipment, pressure fire extinguishing equipment, associated vehicle and extinguishing agent. The LY100 system can be deployed quickly and operated flexibly. Based on such advantages, the indoor fire, exterior thermal insulation layer fire and top platform fire of high-rise building can be extinguished in a timely manner with the LY100 system. In addition, four kinds of firefighting tactics are described in this paper, including one drone operation, double drone cooperative operation, three or more drone cooperative operations, and cooperating with the lifting fire truck. Finally, the experiments are presented to verify the spraying distance of the fire drone system.